REPRESENTASI GAYA HIDUP GENERASI STROBERI PADA INSTAGRAM - Musyorafah Musyorafah; Muhammad Hasyim; Andi Faisal (Jurnal Ilmiah Global Education, 2023)
The purpose of this study is to represent the lifestyle of the strawberry generation on Instagram. The basic theory used is representation theory which is used to analyze the lifestyle of the strawberry generation through identity construction. The results of this study indicate that the strawberry generation displays lifestyle as an identity on Instagram. Identity shown through photos, videos, captions and music. The results of this study indicate that the lifestyle of the strawberry generation in culinary, vacation, gadgets and fashion shows an identity that is like things that are instant, practical, fragile, consumptive, contemporary, and like technology